W-band OFDM for radio-over-fiber direct-detection link enabled by frequency nonupling optical up-conversion - Alavi, Sayed Ehsan (Institute of Electrical and Electronics Engineers Inc., 2014)
A system involving W-band (75-110 GHz) optical millimeter (mm)-wave generation using the external optical modulator (EOM) in a radio-over-fiber (RoF) link is presented for satisfying the requirements for multi-gigabit-per-second data rates. A 90-GHz mm-wave signal was generated by a nonupling (nine times) increase in only a 10-GHz local oscillator by biasing the EOM at its zero level and choosing an appropriate modulation index. To achieve a fast transmission speed wirelessly, high spectral efficiency (SE), and better transmission performance, orthogonal frequency-division multiplexing (OFDM) is used. The bit error rate (BER) and error vector magnitude (EVM) of the system were measured for three different fiber lengths and for a wireless distance of 1-5 m. The results show that the system with the SE of ∼4 (b/s)/Hz and 16-ary quadrature amplitude modulation (QAM) 40-GB/s OFDM signals can be received by the end user with BER less than 3.8 × 10-3 and EVM less than 25% over a 50-km optical fiber and 3-m wireless link.